In che modo i Salmi provengono da Dio? - Witczyk, Henryk (The Biblical Annals, 2015)
The content of the Psalms bears witness to how they are related to and come from God. The Psalms describe different aspects of human experience, such as personal or collective experience of salvation, prophetic word pronounced in the sanctuary, rereading of the old prophecies, sapiential tradition. The psalmists express their various types of religious experience in the context of individual or communal encounter with God, but eventually this experience advances within the history that is guided by the God of the Exodus and of the covenant.